Optimization of static characteristic of Bevel Gear - PATEL, JIGNESH; KHATRI, KHUSHBU; PATEL, MARMIK N; THAKKAR, DARSHAN (IJRDO - Journal of Mechanical And Civil Engineering, 2018)
The main objective of this project is to increase the static characteristics by using composites. First we create paramatric model in creo at various stages and after it will be analysized in the ansys workbanch 14.5. It is observed that Glass filled polyamide composite material is selected as a best material for differential gear box which can be increase the static characteristics. Comparison of various stresses and strain result using ANSYS-14.5 workbanch with Glass filled polyamide composite and Aluminium alloy are also being performed. The model of gear box generated using CREO 3.0 used to perform comprehensive Finite Element Analysis of composite material gear box using ANSYS-14.5 workbench.